The emotional adjustment in the process of restorative art-therapy : the experience of interdisciplinary - Lebedeva, Liudmila D. (Social Welfare: Interdisciplinary Approach, 2014)
Long-term changes in neuropsychological status of the female body (emotional deprivation, depression, neuroses) contribute to the development of cancer. Novelty of the research includes the evidence of influence of art therapy on emotional adjustment of cancer patients, the reliability of laboratory-confirmed levels of oxidative stress and cytokines (regulatory proteins) as a prognostic indicator in the assessment of neuroendocrine cancer patients. Program of Restorative Art Therapy proved efficiency of changes in emotional stability, motivation to recover, improvement life quality of cancer patients.